The non-protein coding breast cancer susceptibility locus Mcs5a acts in a non-mammary cell-autonomous fashion through the immune system and modulates T-cell homeostasis and functions - Smits, Bart MG (BioMed Central, 2011)
INTRODUCTION: Mechanisms underlying low-penetrance, common, non-protein coding variants in breast cancer risk loci are largely undefined. We showed previously that the non-protein coding mammary carcinoma susceptibility locus Mcs5a/MCS5A modulates breast cancer risk in rats and women. The Mcs5a allele from the Wistar-Kyoto (WKy) rat strain consists of two genetically interacting elements that have to be present on the same chromosome to confer mammary carcinoma resistance. We also found that the two interacting elements of the resistant allele are required for the downregulation of transcript levels of the Fbxo10 gene specifically in T-cells. Here we describe mechanisms through which Mcs5a may reduce mammary carcinoma susceptibility. METHODS: We performed mammary carcinoma multiplicity studies with three mammary carcinoma-inducing treatments, namely 7,12-dimethylbenz(a)anthracene (DMBA) and N-nitroso-N-methylurea (NMU) carcinogenesis, and mammary ductal infusion of retrovirus expressing the activated HER2/neu oncogene. We used mammary gland and bone marrow transplantation assays to assess the target tissue of Mcs5a activity. We used immunophenotyping assays on well-defined congenic rat lines carrying susceptible and resistant Mcs5a alleles to identify changes in T-cell homeostasis and function associated with resistance. RESULTS: We show that Mcs5a acts beyond the initial step of mammary epithelial cell transformation, during early cancer progression. We show that Mcs5a controls susceptibility in a non-mammary cell-autonomous manner through the immune system. The resistant Mcs5a allele was found to be associated with an overabundance of gd T-cell receptor (TCR)+ T-cells as well as a CD62L (L-selectin)-high population of all T-cell classes. In contrast to in mammary carcinoma, gdTCR+ T-cells are the predominant T-cell type in the mammary gland and were found to be overabundant in the mammary epithelium of Mcs5a resistant congenic rats. Most of them simultaneously expressed the CD4, CD8, and CD161α markers. In cultured T-cells of Mcs5a resistant congenic rats we found increased mitogen-induced proliferation and production of Th1 cytokines IFNg, IL-2, and Tumor Necrosis Factor (TNF), but not Th2 cytokines IL-4 and IL-6, or Th17 cytokine IL-17 when compared with susceptible control rats. CONCLUSIONS: These data support a hypothesis that Mcs5a displays a non-mammary cell-autonomous mechanism of action to modulate breast cancer risk through the immune system. The resistant Mcs5a allele is associated with alterations in T-cell homeostasis and functions, and overabundance of γδTCR+ T-cells in carcinogen-exposed mammary epithelium.